In Pursuit of Capitalist Agrarian Transition. (July 2016) - Byres, Terence J.
Abstract : This is a contribution to a long‐standing 'conversation' between Henry Bernstein and Terry Byres on capitalist agrarian transition, encompassing the development of capitalist agriculture and capitalist industrialization. Two themes are central: first, the divergence of view with respect to the possible relevance of past transitions for the present (posited by Byres) and the contemporary, pre‐emptive power of globalization (argued by Bernstein); and, second, the basic difference of analytical procedure. There is discussion of how, in India, before 1947, colonialism sought unsuccessfully to replicate an 'English model' of transition in eastern India; and how, throughout India, colonialism through surplus appropriation and remittances to Britain prevented the creation of the underlying structural conditions necessary for successful agrarian transition. Aspects of the nature of the Byres treatment of the Scottish experience of agrarian transition in the eighteenth century are considered, to illustrate the nature of the Byres method. The paper seeks to advance the conversation by clarifying the contrast between the two approaches.